Information resources management : concepts, methodologies, tools, and applications - Information Resources Management Association (Hershey : Information Science Reference, 2010)
'This work is a comprehensive, four-volume reference addressing major issues, trends, and areas for advancement in information management research, containing chapters investigating human factors in IT management, as well as IT governance, outsourcing, and diffusion'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information resources management